Decarbonization technology responsibility to gender equality in the shipping industry: A systematic literature review and new avenues ahead - Assunta Di Vaio; Anum Zaffar; Daniel Balsalobre-Lorente; Antonio Garofalo (Journal of Shipping and Trade (JST), 2023)
This study investigates existing literature on decarbonization technology responsibility for sustainable business models in the shipping industry. Specifically, it considers the relationship between responsible innovation from green technology adoption in decarbonization management practices and gender equality to precisely target how decarbonization technology relates to gender mainstreaming, a key element of Sustainable Development Goal 5 in the UN 2030 Agenda. From the institutional theory perspective, this study conducted a systematic review of 114 articles published in the ISI Web of Science and Scopus databases from 1990 to 2022. The results highlight that green technology adoption can support low-carbon practices and gender equality in the shipping industry by contributing to decarbonization technology responsibility, sustainable business models, and responsible innovation. Ultimately, this study suggests that shipping management should provide training and workshops for women on technology adoption in decarbonization operational processes to support gender quality and technological development. It also presents a new conceptual framework and research propositions on significant issues that are currently neglected. The proposed framework may be treated as a decarbonization technology responsibility guideline in shipping management that can reshape the organizational culture to promote gender equality.
Keywords: 650; Decarbonization management practices; Green technology; Institutional theory; Responsible innovation; Sustainable business models; Sustainable Development Goal (SDG) 5